Pelatihan Pembuatan Eco-Enzyme Menjadi Hand Sanitizer dan Pupuk Cair Organik di Desa Pucung - Kurniawan, Muhammad Rifki; Adjie, Rofiq Perwira; Akbar, Ilham Rizqi; Nugraha, Salis Azkia; Nalendra, Bomaseta Aadiyaatloka (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
In 2020, waste in Indonesia reached 67.8 million tons, an increase of around 0.8 million tons from the previous year. As for the Special Region of Yogyakarta, it was recorded that there were around 6,917 tons of waste. This waste problem is also experienced by Pucung Hamlet, Bantul. This community service activity aims to solve the waste problem in Pucung Village and produce alternative natural products as hand sanitizers and organic liquid fertilizer during the COVID-19 pandemic. The implementation method begins with counseling techniques, training, and science and technology assistance. Innovation and creativity in making eco-enzymes are present as the best solution for housewives in processing organic waste into something more useful. Housewives can be more productive, can save more expenses and indirectly help the cleaners in sorting household waste into organic and inorganic waste. The training activity on making eco-enzyme was successfully carried out with indications of the enthusiasm of the community being quite large and increasing the awareness of the partner community about waste management. Through this activity, it is hoped that housewives can be more creative and innovative in processing household waste in the future.